GOOD FAITH ON ANIMAL CARE AGREEMENT : STUDY OF ARTICLE ABOUT TRANSFER OF ANIMAL OWNERSHIP - Umar Haris Sanjaya; Mirza Ajeng Thiasari (Universitas Muhammadiyah Tangerang, 2022)
Abstract: This study aims to analyze and determine the good faith in the use of clauses on the transfer of animal ownership in animal care services business actor in GPSPK Depok. This study provides an analysis for the implementation of good faith in animal care contract. Problem formulations for this journal are; How is the implementation of good faith in the use of the transfer of animal ownership clause in animal care services business actor? and is the implementation of good faith in the transfer of animal ownership is in accordance with the good faith of contract implementation? This research is normative legal research accompanied by supporting data. The research data was collected through literature study. The analysis was carried out using qualitative methods. Based on the research results, it is concluded that: First, the service user binds himself to an animal care contract that contains the clauses of the transfer of animal ownership. However, the business actor does not execute these clauses, even though the business actor has the opportunity to do so. Second, the clauses of the transfer of animal ownership are against the good faith of contract implementation which refers to: fairness, equity, and reasonableness.